2002
DOI: 10.2135/cropsci2002.0507
|View full text |Cite
|
Sign up to set email alerts
|

Tifway Bermudagrass Response To Potassium Fertilization

Abstract: cold-hardiness (Beard, 1982). Gilbert and Davis (1971) reported that a 4N:6K ratio provided excellent shoot Potassium fertilization rates used for 'Tifway' bermudagrass [Cynogrowth of 'Tifdwarf' and 'Tifgreen' bermudagrasses don dactylon (L.) Pers. ϫ C. transvaalensis Burtt-Davy] vary greatly among turfgrass managers and there is no consensus as to the actual following cold treatment, although shoot growth at quantity required or as to the best Potassium (K) source to use. Effects the 4N:6K ratio was not sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
24
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 2 publications
(3 reference statements)
8
24
3
Order By: Relevance
“…Mehall et al (1984) found photosynthate partitioned to roots to be positively correlated to the size of the root system and inversely related to clipping production. Similar to the effects of K on CY, the effects of K on rooting in this current study and as reported elsewhere have been minimal (Snyder and Cisar, 2000;Sartain, 2002). Similar to the effects of K on CY, the effects of K on rooting in this current study and as reported elsewhere have been minimal (Snyder and Cisar, 2000;Sartain, 2002).…”
Section: Rooting By Depthsupporting
confidence: 80%
See 2 more Smart Citations
“…Mehall et al (1984) found photosynthate partitioned to roots to be positively correlated to the size of the root system and inversely related to clipping production. Similar to the effects of K on CY, the effects of K on rooting in this current study and as reported elsewhere have been minimal (Snyder and Cisar, 2000;Sartain, 2002). Similar to the effects of K on CY, the effects of K on rooting in this current study and as reported elsewhere have been minimal (Snyder and Cisar, 2000;Sartain, 2002).…”
Section: Rooting By Depthsupporting
confidence: 80%
“…Petrovic et al (2005) and Fitzpatrick and Guillard (2004) have also reported similarly low soil test K levels of 50 to 60 mg kg −1 , with no CY response observed despite testing low for soil K. They have attributed this lack of a response in shoot growth to K fertilization to be related in part to the important role that N contributes to soil test K interpretation. In addition, many have suggested the need to reevaluate current soil test K recommendations because they may be too high for turfgrass (Watschke et al, 1977;Sartain, 2002;Fitzpatrick and Guillard, 2004;Petrovic et al, 2005). However at 343 kg N and year 2008 (Table 4), soil test K levels of 80 mg kg −1 were associated with a positive CY response to K fertilization (P = 0.063) and CY increased from 3.3 to 5.2 g dry wt.…”
Section: Interrelationships Between Nitrogen and Potassium Fertilizatmentioning
confidence: 99%
See 1 more Smart Citation
“…Webster and Ebdon (2005 and Fitzpatrick and Guillard (2003) also reported no signifi cant relationship between tissue K and soil K levels in response to N and K. Signifi cant nonlinear responses to N (NQ) and K (KQ) were observed with tissue K concentrations in 2006 and 2007 (Table 13). Numerous researchers have also observed tissue K to be nonlinear in response to K fertilization (Sartain, 2002;Fitzpatrick and Guillard, 2003;Webster and Ebdon, 2005) and have found clipping yield not to be correlated with tissue K. No signifi cant correlation was detected between soil and tissue K with either shoot growth or wear tolerance.…”
Section: Shoot Tissue Potassium and Soil Potassiummentioning
confidence: 99%
“…Yearly N rates of 343 to 441 kg N ha -1 yr -1 are not within the N range typically recommended for sports turf managers (Puhalla et al, 1999). Sartain (2002) also reported the need to adjust down Mehlich-1 soil test interpretations to as low as 30 mg K kg -1 soil in bermudagrass (Cynodon dactylon L.). For the silt loam soil used in this study and at the N rates ordinarily applied by sports turf managers, Morganextractable K levels of 70 mg K kg -1 soil are adequate for optimum shoot growth and wear tolerance in perennial ryegrass.…”
Section: Shoot Tissue Potassium and Soil Potassiummentioning
confidence: 99%